Legal Protection of Workers' Rights for Worship from the Perspective of Positive Criminal Law and Islamic Criminal Law - Arifuddin Muda Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine how the provisions of the implementation of workers' rights to worship. Starting from several violations of workers' rights to worship that occurred in Indonesia. This study will also discuss the legal consequences if a person/ entrepreneur obstructs the workers 'right to worship, as well as factors that hinder the fulfillment of workers' rights to worship. This research uses a type of normative and library research, using a descriptive analytic type of research, which focuses on cases of violations of workers' rights to worship that have previously occurred in Indonesia, and then analyzed based on statutory regulations and Islamic law. The results of this study indicate that the rights of workers to worship have been regulated and guaranteed in various legal instruments in Indonesia, both according to Islamic law and statutory regulations. Every worker and employer is required to know the rights and obligations of workers and employers, as well as to know the factors that hinder the fulfillment of workers' rights to worship.